Aligning Chemistry Learning with Medical Laboratory Technology Vocational Competencies: A Needs and Curriculum Accommodation Analysis - Rahmani, Ridha Ariandini; Anwar, Sjaeful; Gumilar, Gun Gun (Hydrogen: Jurnal Kependidikan Kimia, 2026)
The chemistry content provided in the Merdeka Curriculum is expected to support students' vocational competencies. However, its suitability for the learning needs of the Medical Laboratory Technology (Teknologi Laboratorium Medik/TLM) vocational program has not been systematically evaluated. This study aimed to evaluate the extent to which the chemistry contents required for the TLM program are accommodated in the learning objectives and teaching materials of the Proyek IPAS and Basic Medical Laboratory Technology (DDTLM) subjects. This study employed an evaluative research design with a qualitative approach. Data were collected through document analysis of the learning objectives and teaching materials of the Proyek IPAS, DDTLM, and Laboratory Support Services subjects, as well as semi-structured interviews with teachers. The data were analyzed using Qualitative Content Analysis (QCA) to identify the chemistry contents required for TLM vocational competencies and to evaluate their accommodation in the analyzed curriculum documents. The findings indicate that the identified chemistry contents are only partially accommodated in the Proyek IPAS and DDTLM subjects. Proyek IPAS primarily provides fundamental chemistry contents as general scientific knowledge, whereas DDTLM introduces several concepts through laboratory activities. Nevertheless, several chemistry contents relevant to laboratory procedures and clinical examinations were found to be insufficiently accommodated or presented without authentic TLM contexts. Based on these findings, a synthesis of the identified chemistry contents and their relevant TLM contexts was developed to summarize the chemistry knowledge required within the scope of the analyzed curriculum. The study concludes that the analyzed curriculum documents only partially accommodate the chemistry contents required to support learning in the TLM context. The findings provide a reference for future efforts to contextualize chemistry learning and support the development of chemistry teaching materials for the Medical Laboratory Technology program.